Osseointegration effects of whey protein (histological and histomorphological observations): An experimental study on rabbits - Kamil, Nawar B; AL-Ghaban , Nada M H; Aamery , Amaar (Journal of Baghdad College of Dentistry, 2023)
Background: Whey protein is the green-yellow colored, liquid portion of the milk, and it is also called the cheese serum, it is obtained after the separation of curd, during the coagulation of the milk. It contains a considerable amount of α-helix pattern with an evenly distributed hydrophobic and hydrophilic as well as basic and acidic amino acids along with their polypeptide chain. The major whey protein constituents include β-lactoglobulin (β-LG),α-lactalbumin (α-LA), immunoglobulins (IG), bovine serum albumin (BSA), bovine lactoperoxidase (LP), bovine lactoferrin (BLF) and minor amounts of a glycol macro peptide (GMP). Osseointegration can be defined as a process that is immune driven which leads to the formation of the new bone surrounding the surface of the implant rather than a pure response of the bone. Titanium can activate a balance recognized to be tolerogenic with a peri-implant tissue leading to a "foreign body equilibrium (FBE)" response. Materials and methods: Twelve adult male white New Zealand healthy rabbits were used in this study, the animals were divided into two groups according to the time of scarification as follows; 2 and 6 weeks after the implantation (6 rabbits will be sacrificed for each group). Results: Statistical analysis showed that there is a highly significant difference in all parameters between the experimental group and control group at 2 weeks and 6 weeks periods. Histological results at 2 weeks period showed thread formation in whey protein and control group, distribution of osteocyte cells and osteoblast was higher in whey protein, and the bone trabecular area was also larger in whey protein groups but at 6 weeks showed mature bone in whey protein groups while in control group still woven bone. Conclusions: Whey protein is an effective in osseointegration because it enhances bone formation.